Pengembangan E-Modul Makanan Asia Timur Berbasis Flip Builder Untuk Siswa Program Keahlian Kuliner SMKN 1 Cerme Gresik - Chlara Amanda; Mauren Gita Miranti; Any Sutiadiningsih; Asrul Bahar (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the feasibility of the Flip builder-based East Asian food E-Module in terms of materials and media, and the response of users of the Flip builder-based East Asian food E-Module. This research is a research and development (research and development) with a 4D model (Define, Design, Develop, Disseminate). The population in this study were students of the Bachelor of Culinary Education study program class of 2019 at Surabaya State University. The data collection technique uses a questionnaire validating the feasibility of materials and media which is calculated using the Aiken V formula and the user response questionnaire is calculated using percentages. The results of the research show that: (1) Flip builder-based East Asian food e-module is feasible to use. This was obtained from the results of the assessment by the validator of material experts and media experts of 0.872 in the very good/high product category and the reliability test results obtained a reliable level (???? ????) of expert judgment of 0.902 which means that the East Asian food emodule based on flip builder is reliable from the standpoint content and construct. (2) The flip builder-based East Asian food e-module obtained student responses with a score of 84.9 indicating that the flip builder- based East Asian food e-module for Culinary Education S1 students is included in the very attractive category so it can be used as an ingredient. teach in East Asian Food studies.